‘I represent a country that wants peace.’ Compassionate leadership in Maia Sandu’s address on the 77th Session of the UN General Assembly - Wawrzyński, Patryk (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2024)
The paper discusses the case study of Moldovan President Maia Sandu’s speech in the general debate during the 77th Session of the United Nations General Assembly in September 2022 in the context of the war in Ukraine. It considers compassionate leadership as a communicative strategy in political crisis management and investigates the congruency between the contents of narrative and nonverbal immediacy as its measure in political communication. The presented study is based on data collected with a content analysis of the address and the automated coding of facial expressiveness with FaceReader 9 (Noldus IT) in the recording of Sandu’s speech. The timeline analysis compared the narrative with the intensity of neutrality, basic emotions, sympathy, pain, attention, emotional arousal, valence, and the RPPG-estimated heart rate, describing displayed emotionality, motivation, and physiological stress. The standardized results suggest increased nonverbal signaling of emotions, oriented towards surprise, considered a substitute expression of compassionate responsiveness, sympathy, and sadness, while violent emotions (anger, disgust, and contempt) were marginalized. Moreover, the analysis provided evidence of the consistent, verbal, and nonverbal presence of core assets of compassionate leadership in Sandu’s address to the UN General Assembly. Artykuł przedstawia studium przypadku wystąpienia Prezydent Mołdawii Mai Sandu w czasie debaty na 77. Sesji Zgromadzenia Ogólnego Narodów Zjednoczonych we wrześniu 2022 roku w kontekście wojny w Ukrainie. Podejmuje się zagadnienie przywództwa opartego na współczuciu jako strategii komunikacyjnej zarządzania kryzysem politycznym, badając spójność treści narracji i bezpośredniości niewerbalnej jako jego wyznacznika w komunikacji politycznej. Badanie wykorzystuje dane zgromadzone w analizie treści wystąpienia i automatycznym kodowaniu ekspresji mimicznych z użyciem systemu FaceReader 9 (Noldus IT) do analizy nagrania wypowiedzi Sandu. Analiza linii czasowej pozwoliła porównać opowieść z intensywnością neutralności, emocji podstawowych, sympatii, bólu, uwagi, pobudzenia emocjonalnego, wektora emocjonalnego oraz estymacji tętna (RPPG), dokładnie opisując ujawnione sygnały odczuwanych emocji, motywacji i stresu fizjologicznego. Ustandaryzowane wyniki wskazują na podwyższoną sygnalizację emocji, zorientowaną na zaskoczenie – uznane za zastępczą ekspresję dla współczucia – sympatię i smutek, podczas gdy emocje przemocowe (gniew, obrzydzenie i pogarda) były ograniczone. Ponadto, analiza dostarczyła dowodów na spójną, werbalną i niewerbalną, obecność w wystąpieniu Sandu kluczowych zasobów przywództwa opartego na współczuciu.
„Reprezentuję kraj, który pragnie pokoju”. Przywództwo oparte na współczuciu w wystąpieniu Mai Sandu na 77. Sesji Zgromadzenia Ogólnego ONZ
Keywords: nonverbal communication; sympathy; surprise; compassion; political communication; public speaking; komunikacja niewerbalna; sympatia; zaskoczenie; współczucie; komunikacja polityczna; wystąpienia publiczne